Migration and health study: a socio-ecological analysis of sexual health among migrants in Manitoba, Canada - Rusty Souleymanov; Bolaji Akinyele-Akanbi; Chinyere Njeze; Patricia Ukoli; Paula Migliardi; John Kim; Michael Payne; Laurie Ringaert; Gayle Restall; Linda Larcombe; Nathan Lachowsky; Mohammad Nuruzzaman Khan; et al. (BMC, 2023)
Abstract Background To develop effective public health policies, programs, and services tailored to the unique sexual health needs of migrant populations, it is essential to understand the myriad socio-ecological factors that influence their sexual health. This qualitative community-based participatory study aimed to explore factors influencing migrants' sexual health at different socio-ecological levels in a Canadian setting. Methods Participants (n = 34) from African, Caribbean, Black; Latin American; South Asian; Middle Eastern, as well as East and Southeast Asian communities were recruited across Manitoba using printed flyers, community organizations, and social media. Individual interviews, conducted in English, French, Mandarin, Cantonese, Tagalog, Arabic, Swahili, and Tigrinya languages, explored questions relating to sexual health and experiences with service providers. Data were analyzed using reflexive thematic analysis and socio-ecological systems theory. Results The study uncovered a range of individual, interpersonal, institutional, and socio-structural factors that affect the sexual health of migrants in Manitoba. Individual factors such as sexual health knowledge and testing practices, interpersonal factors like the type of sexual partnerships, institutional factors such as sexual health information needs, language, and service access barriers, and structural-level factors like gender norms and HIV stigma exerted a significant influence on the sexual health practices of study respondents. Sexual health awareness was influenced by various factors including length of time in Canada and involvement in community-based services. Study respondents identified issues related to access to HIV testing and sexual health information, as well as language barriers, racism in healthcare, and HIV stigma. Gender and social norms played a significant role in discouraging communication about sex and safer sex practices. Conclusions The study highlights the complex interplay of factors that influence the sexual health of migrants, and the need for targeted sexual health awareness campaigns and provision of sexual health information in languages spoken by migrants. Public health interventions focused on improving the sexual health outcomes for migrants should consider the socio-ecological elements identified in this study. These findings can inform public health campaigns to increase access to services and address sexual health inequities among migrant communities in Canada.